Development of an enzyme-linked immunosorbent assay for newborns dried blood spot thyroglobulin - Fuentes Peña, Camilo.; Opazo Delgado, María Cecilia.; Méndez, Luis; Riedel, Claudia A.; Hauquier, Bernard; Marcelis, Lionel; Cotton, Frédéric; Moreno Reyes, Rodrigo. (BioScientifica, 2024)
Background: Thyroglobulin (Tg) is a biomarker of iodine status. Newborn Tg is a more sensitive marker than neonatal TSH in detecting variations in iodine intake. This study aims to validate an enzyme-linked immunosorbent assay (ELISA) for Tg determination on dried blood spots (DBS) in newborns. This study also sets out to assess the stability of Tg and the influence of newborns’ hematocrit on Tg determination. Methods: A commercially available ELISA Tg assay was adapted for use on DBS. DBS-Tg in cord blood was measured in 209 newborns delivered from healthy euthyroid pregnant women. Sensitivity, linearity, repeatability, and intermediate fidelity were determined using the appropriate standards and quality control materials. Results: The limit of detection of the DBS-Tg assay was 2.4 µg/L, and the limit of quantification was 5.8 µg/L. Repeatability and intermediate fidelity were 7.7–8.3% and 11.0–11.2%, respectively. The median cord plasma Tg and DBS-Tg values in newborns were not significantly different, 30.2 (21.3–44.4) µg/L and 31.6 (19.3–48.7) µg/L (P = 0.48) with the ELISA, respectively, and 76.5 (40.0–101.5) µg/L with the Elecsys assay with an R = 0.88. DBS-Tg concentrations decrease with increasing hematocrit values (P < 0.05). DBS-Tg values were stable at a concentration of 25 µg/L for 12 months at −20ºC and 4ºC. Conclusion: This DBS-Tg assay demonstrated good analytical performance over a wide range of Tg concentrations, suggesting it is well suited to detecting variations in Tg concentrations. Studies comparing populations with different prevalence of anemia should consider the effect of hematocrit on DBS-Tg determination. The availability of a DBS-Tg assay for newborns makes it possible to integrate iodine status monitoring with newborn screening for inherited metabolic diseases.
Keywords: Dried blood spot; ELISA; Newborn; Yodo; Thyroglobulin